Reclaiming women community: The Balee Inong initiative and grassroots gender politics in Banda Aceh - Lestari, Yeni Sri; Saputra, Akmal; Sopar, Sopar; Masrizal, Masrizal; Syuhada, Ilham (SIMULACRA: JURNAL SOSIOLOGI, 2025)
This research examines Balee Inong’s objectives as a women’s struggle community in Banda Aceh City towards increasing the role of women in the public sector. Although Balee Inong has empowered women in Banda Aceh City, one community, to fight for women’s rights, Balee Inong has not shown significant results in involving most women actively engaged in public spaces and decision-making subjects. This study uses a qualitative case study approach to analyze the roles and challenges of Balee Inong, which focuses on empowerment and work programs in Balee Inong. The study findings indicate that Balee Inong’s role has not yet been maximized due to several factors related to women’s political identity awareness, social construction, and patriarchal culture. These obstacles hinder women’s more significant role in the public sphere. This study concludes that although Balee Inong in Banda Aceh City provides opportunities for increasing women’s participation, it has not had a substantial impact on reaching all women in Banda Aceh City. The limitation of this study is that it has not fully reached women in Banda Aceh City who represent Balee Inong because of different perspectives and not yet significantly represented. This study highlights the need for more realistic efforts through comprehensive empowerment to distribute the understanding and goals of Balee Inong in the public domain.